Strategi Pembelajaran Baca Al-Quran Melalui Metode Ngalah pada Siswa Kelas 2 Sekolah Dasar Islam Perwanida Nurul Fajar, Komplek Departemen Agama Pabuaran, Bojonggede Bogor - Efrita Norman; Siti Chaerul Barijah ; Siti Aminah; Wiwi Uswatiyah (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
Reading the Koran is mandatory for students at SDI Perwanida Nurul Fajar because it is part of practicing Islamic teachings. In accordance with Government Regulation of the Republic of Indonesia number 55 of 2007 concerning Religious and Religious Education that religious education aims to develop the ability of students to understand, appreciate and practice religious values, in the Content Standards of Article 6 number 2 that Religious Education encourages students to obey the teachings of religion in everyday life. The type of this research is descriptive qualitative research because this research describes how the strategy of learning to read the Koran through the NGALAH method in grade 2 students of SDI Perwanida Nurul Fajar involving the teacher of SDI Perwanida Nurul Fajar as the object of research. The results of this study are in accordance with PP RI No. 55 of 2007 concerning religion and religion as well as about the Content Standards of article 6 number 2. That it can be applied to Perwanida Nurul Fajar Islamic Elementary School students in reading the Koran using the NGALAH method so that students read the Koran according to Proven letters and harakat signs every Monday to Thursday all students deposit the reading of the Koran to their respective teachers, the sorogan system uses the NGALAH method Keywords: Learning Strategy, Reading Al Quran, NGALAH Method, Students